Deepening the single market and enhancing EU democracy: A justification for 'more Europe'. Issue 1 (April 2019) - Pelagidis, Theodore; Mitsopoulos, Michael
The need for 'more Europe' stands out today in an international environment that is contaminated by populism, authoritarianism and demagogy. Consequently, when confronting political radicalism, the domains that the EU should henceforth concentrate on in a positive way must be specified, explaining practically and with pragmatism the reasons for 'more Europe'. In particular, the EU must deliver concrete benefits that citizens can see in their daily lives, but, at the same time, it has to give them more democratic control over their representation in EU bodies and in the way EU law is shaped and implemented. To accept such progress, the EU must first recognise the critical flaws in its current economic and political architecture, before proceeding to adopt policies that will adequately restore the dynamism of the European dream, leading to a more efficient and just EU. More democracy will help gather support, and ensure renewed progress towards a closer Union in which the single market is meaningfully deepened.